THYROID SURGERY: FROM ACADEMIC FOUNDATIONS TO MODERN PRACTICE (Vietnam Journal of Community Medicine, 2026)
Objective: To summarize the fundamental concepts of contemporary thyroid surgery, review recent technological developments, and discuss current issues encountered in clinical practice.Methods: This narrative review was prepared through a comprehensive appraisal of clinical practice guidelines, authoritative textbooks, and PubMed-indexed publications concerning thyroid surgery and surgical anatomy.Results: The introduction of energy-based devices, intraoperative neural monitoring, near-infrared fluorescence imaging, and minimally invasive techniques has enhanced surgical safety. Nevertheless, successful preservation of the recurrent laryngeal nerve, the external branch of the superior laryngeal nerve, and the parathyroid glands remains the principal determinant of favorable postoperative outcomes.Conclusions: Contemporary thyroid surgery relies on the integration of anatomical expertise, surgical experience, and technological advances. Careful adherence to fundamental surgical principles continues to be the key to achieving safe procedures while preserving postoperative function.
Keywords: Thyroid surgery, recurrent laryngeal nerve, external branch of the superior laryngeal nerve, parathyroid glands, intraoperative neural monitoring, TOETVA.